Legal Aspects of Merging Limited Liability Companies in Company Law by Merger - Atika Sunarto; Muhammad Ali Adnan (IHSA Institute, 2019)
In general, the goal of a merger is to obtain synergy or added value. The added value in question is more long-term compared to the added value that is temporary. Therefore, there is no synergy of a merger that cannot be seen shortly after the merger occurs. But it takes quite a long time. The synergy that occurs as a result of a merger of business bias in the form of ups and downs of economic questions, and financial synergy in the form of capital increase. The advantage of merger is that the takeover through a merger is simpler and cheaper compared to the other takeovers while the merger's shortcomings are that there must be approval from the shareholders of each company, whereas to obtain the agreement requires a long time. The merger strategy is an alternative to expanding the business.